Problems of establishment and activity of the antituberculosis service in Kazakhstan during Virgin Lands campaign (early 1960s) - Orazbayeva, A.; Kozina, V.; Mazhitova, Zh.; Kurbanova, D. (E3S Web of Conferences 371, 2023)
The paper notes that after the formation of the Virgin Lands area in December 1960, the local health authorities faced a pressing issue of solving the problems of tuberculosis spread among the local population, as well as people resettled there. Tuberculosis, like other infectious diseases, was widespread in Kazakhstan. The establishment of tuberculosis dispensaries and the creation of fluorography and X-ray machines have provided an opportunity to expand preventive measures for the examination and detection of tuberculosis patients. The health authorities of the Virgin Lands area considered work in this direction as improving the quality of medical care. However, the quality of treatment was often reduced due to the facts that the treatment regimen was violated in several dispensaries, there were not enough specialists, control over the full and long-term treatment of tuberculosis patients was not imposed. The authors of the paper concluded that insufficient and not universal organization of medical care was one of the reasons for the high incidence of tuberculosis among the population.